State Financial Rescue Through Return of Replacement Money In The Case of Road Landscaping Project In Fiscal Year 2022-2023 (Case Study of The Medan District Attorney's Office) - Silalahi, Eirene Clarisa Br.; Siallagan, Haposan; Situmorang, Samuel (Dinasti Research, 2026)
Efforts to rescue state finances through a compensation mechanism for the 2022–2023 Road Landscape Arrangement project in Medan City, which has resulted in potential losses to the Regional Revenue and Expenditure Budget due to work that does not comply with technical specifications. This study uses an empirical normative legal method with a statutory regulatory approach and case study analysis. The results show that the Medan District Attorney's Office has a strategic role in the process of recovering state losses through criminal law mechanisms and through non-litigation legal assistance in its capacity as a State Attorney. The return of funds to the regional treasury is a form of recovery of state losses, but this action does not eliminate criminal liability if the elements of the crime are still met. The return of losses can only be used as a mitigating consideration for judges in issuing decisions, so that the law enforcement process must still be carried out based on the principles of legality and legal certainty.